Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2013
DOI: 10.1186/2194-0517-2-6
|View full text |Cite
|
Sign up to set email alerts
|

Electrospun eri silk fibroin scaffold coated with hydroxyapatite for bone tissue engineering applications

Abstract: Natural biomaterials such as collagen, silk fibroin, and chitosan, and synthetic biopolymers such as polylactic acid, polycaprolactone, polyglycolic acid, and their copolymers are being used as scaffold for tissue engineering applications. In the present work, a fibrous mat was electrospun from eri silk fibroin (ESF). A composite of hydroxyapatite (Hap) and the ESF scaffold was prepared by soaking the ESF scaffold in a solution of calcium chloride and then in sodium diammonium phosphate. The average tensile st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
43
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(47 citation statements)
references
References 24 publications
(35 reference statements)
2
43
1
Order By: Relevance
“…Additionally, the porosity of the material may play an important role in the water uptake; the substitute is considered a non-porous material, but the ionic exchange with the medium provokes its degradation and the formation of micro-porosities that allow water uptake [6,49]. Furthermore, our water uptake values were lower compared to those obtained in other studies on materials made of fibroin and calcium phosphates, which are usually between 42% and 70% [46,47].…”
Section: Characterization Of Sf/nha Substitutes 1) In Vitro Degradcontrasting
confidence: 54%
See 2 more Smart Citations
“…Additionally, the porosity of the material may play an important role in the water uptake; the substitute is considered a non-porous material, but the ionic exchange with the medium provokes its degradation and the formation of micro-porosities that allow water uptake [6,49]. Furthermore, our water uptake values were lower compared to those obtained in other studies on materials made of fibroin and calcium phosphates, which are usually between 42% and 70% [46,47].…”
Section: Characterization Of Sf/nha Substitutes 1) In Vitro Degradcontrasting
confidence: 54%
“…4c and 4d) were similar among replicates, as in the degradation test, noting the lack of a direct relationship between the concentration of fibroin and the water uptake. Fibroin is a hydrophobic polymer, while HA is hydrophilic [46,47]. Although there is no point of comparison to determine whether these values are favorable or not, a high percentage water uptake is not beneficial in injectable bone substitutes, since it directly influences their degradation by collapsing the material, mainly when it is hydrophilic, as is the case of HA; in this case, the addition of small percentages of fibroin allows a moderate water uptake due to its hydrophobic nature [46,48].…”
Section: Characterization Of Sf/nha Substitutes 1) In Vitro Degradmentioning
confidence: 99%
See 1 more Smart Citation
“…However, blending with more than 30 % (by weight) of cellulose acetate, the spinning process was seriously deteriorated producing discontinuous and tacky fibers with beads and dendritic structures. It was also observed that the thermal and mechanical properties were improved by the addition of cellulose acetate up to 10 % [173].…”
Section: Electrospinning Of Silk Fibroinmentioning
confidence: 89%
“…HA is the main inorganic component of natural bone and has biocompatible, biodegradable, and osteoconductive properties [89,90]. It provides higher mechanic strength and stability in the membrane [91].…”
Section: Chitosan Hydroxyapatite and Growth Factorsmentioning
confidence: 99%